Avances recientes en HIV/SIDA: Patogénesis, historia natural y carga viral. - Campo, Rafael E (2013)
Results of recent investigations have given us a new understanding of the pathogenesis of HIV infection. This findings provide us with a kinetic model of pathogenesis in which continuous, high-grade viral replication. This findings provide us with a kinetic model of pathogenesis in which continuous, high-grade viral replication is the principal force driving the destruction of CD4 lymphocytes. This knowledge will lead us to design better treatment strategies directed to curtail viral replication and prevent the emergence of viral resistance, and the use of combination antiretroviral therapy is a first example of these new strategies. The concept of viral load is introduced, and we discuss the usefulness of viral load in the clinical prognosis of this disease, and its use as an aid in the decision-making process when starling or mordifyng antiretroviral therapy in our patients.